Newborn Care Practices by the Mother / Care Givers and Their Knowledge about Signs of Sickness of Neonates (Bangladesh Journal of Child Health, 2012)
Background: Despite proven cost effective intervention, there has been little change in neonatal mortality. In Bangladesh neonatal mortality accounts for two third of infants death. About 90% deliveries take place in home and majority of neonatal death are taking place within 7 days of birth. Information about reasons for delivering at home and newborn care practices will be useful to undertake simple intervention measures by policy makers.Aims and objective: To see the knowledge, perception and behaviour of mothers towards their normal and sick newborn.Methods: A cross sectional study was carried out in Dhaka Shishu Hospital from June to November, 2007. A semistructured, pretested questionnaire was used to interview mothers attending inpatient (IPD) and outpatient department (OPD) of hospital.Results: A total 198 mothers were interviewed. Home deliveries were 35.5% and Institutional were 64.5%. Among the Institutional deliveries 35% (44 out of 127) were planned and tried first at home, but when failed mothers were taken to hospital. Majority (86%) of home deliveries were conducted by Dai/relatives. Umbilical cord was cut with new/boiled blade in 85% of home deliveries and household knife was used in 4% cases. Birth place were not at all heated in all home deliveries. In 32 % of home deliveries babies were given bath within 1 hour of birth and it was 15% in case of hospital deliveries. Forty-eight percent babies of home deliveries were wrapped within 10 minutes. Prelacteal feed was given in 51% of home deliveries in comparison to 23% of institutional deliveries. The rate of initiation of breast feeding within one hour of birth was 52% in home and 35% in institutional deliveries. In all cases breast milk was given within 48 hours. Main reasons cited for delivering at home were preference (43%) and fear about hospital (39%). In case of educated (graduate) mothers 72% deliveries took place at hospital. Less feeding (56%), vomiting (42%), less movement (32%), fever (29%) and cough (27%) could be recognized by mothers as signs of sickness.Conclusion: Home deliveries and poor newborn care practices are commonly found in this study. Traditional birth attendants should be adequately trained as they are conducting majority of home deliveries. Female education is very important to reduce home delivery as it is seen that deliveries of educated mothers are taking place in hospital. High risk traditional newborn care practices like delayed wrapping, early bathing, use of oil in umbilical stump and prelacteal feeding need to be addressed. This study also found that knowledge to identify sickness in newborn is still poor.DOI: http://dx.doi.org/10.3329/bjch.v35i3.10497  Bangladesh J Child Health 2011; Vol 35 (3): 90-96